2009
DOI: 10.4103/0972-0707.58338
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fracture resistance of endodontically treated teeth using different coronal restorative materials: Anin vitrostudy

Abstract: Aim/Objective:To evaluate the in vitro effect of bonded restorations on the fracture resistance of root canal-treated teeth.Materials and Methods:One hundred twenty extracted, maxillary, permanent premolars were collected. After preparing the access cavity, the teeth were biomechanically prepared and obturated. Samples were divided into six groups based on the type of restorative material used to restore them. Teeth were embedded in acrylic resin and their fracture strength was measured using a Universal Testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 20 publications
0
21
0
2
Order By: Relevance
“…Bonded composite restorations can be considered as the first choice for coronal restorations as they play a vital role in increasing the fracture resistance of endodontically treated teeth. [ 4 ] Furthermore, it has been shown that direct and indirect cusp coverage adhesive restorations can significantly increase the fracture resistance of endodontically treated teeth. [ 5 ] Bonding endodontic obturation materials to radicular dentin is another approach to increase fracture resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Bonded composite restorations can be considered as the first choice for coronal restorations as they play a vital role in increasing the fracture resistance of endodontically treated teeth. [ 4 ] Furthermore, it has been shown that direct and indirect cusp coverage adhesive restorations can significantly increase the fracture resistance of endodontically treated teeth. [ 5 ] Bonding endodontic obturation materials to radicular dentin is another approach to increase fracture resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their low elastic modulus, composite resins can transmit stresses produced by compressive forces to adjacent dental tissues, thus reinforcing weakened tooth structure. [ 17 ] In the present study, Nanohybrid composite was used, which has high filler content, which improves its mechanical properties. Results are similar to the study by Aboobaker et al .…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, this approach is invasive and will results in removal of large amounts of sound tooth structure. Composite resin has been chosen as one of the direct permanent restorations for endodontically treated teeth due to the fact that it performed better in term of fracture resistance and is able to reinforce weakened tooth structure ( 3 , 7 ). Besides, current adhesive technology also fulfilled the goal of conserving remaining tooth structure and reducing the amount of intervention needed ( 8 ).…”
Section: Introductionmentioning
confidence: 99%